Association of new fungal species with leaf spot and blight of sunflower and cloning of their ribosomal RNA genes - S.K. SINGH and B.M. KHADI, R.L. CHAVHAN, P.K. CHAKRABARTY*, F.S. PATIL, H.B. PATIL (Indian Phytopathology, 2008)
Twenty four leaf spot and blight infected samples of sunflower were collected from Rahuri, Parbhani, Latur and Pune districts of Maharashtra. Several fungal species were isolated from the infected samples, which were purified by single spore or hypha I tip methods. These include Alternaria alternata (MTCC 7202), Alternaria dianthicola (MTCC 7203), Alternaria helianthi, A. longipes (MTCC 7150), Bipolaris australiensis (Syn. Dreschslera australiensis, MTCC 7215) and Phoma helianthi. The pathogenicity of the fungi was tested on sunflower individually. This is the first report of association of A. dianthicola, A. longipes and B. australiensis with leaf spot of sunflower. The ribosomal RNA genes of A. alternata (DO 156340), A. dianthicola (AY 923859), A. helianthi (DO 156343), A. longipes (DO 156338) and B. australiensis (AY 923860) have been cloned. The sequences are being exploited to develop species-specific primers for diagnosis of these pathogens.